Philosophy And Science From Western And Islamic Perspectives - Bintang Arif Samudra; Febby Adinda; Azizah Hanum OK (Jurnal Multidisiplin Sahombu, 2025)
Research This aiming For analyze meaning  philosophy and science in Western and Islamic perspectives, with highlight equality as well as the difference between both. Philosophy, both in both Western and Islamic traditions, neither only focus on questions fundamental such as “ what ” and “ how,” but also “ why,” with dig understanding deep about phenomenon physical and metaphysical through rationality and logic. Science in Western perspective defined as knowledge systematically obtained through observation, testing, and analysis objective, while in Islamic perspective, science covers aspect physical and metaphysical in harmony with revelation divine. With use method studies literature and approaches descriptive analysis, research This compare view second tradition in a way deep. The result show that Western philosophy emphasizes rationality and freedom individual, whereas Islamic philosophy integrates reason and revelation For build coherent understanding about reality. Western science focuses on the study empirical in nature physical, while Islamic science includes spiritual and transcendental dimensions. Analysis difference epistemological, ontological, and methodological This give contribution significant in understand view second perspective about reality, knowledge, and values life, at the same time enrich discourse intellectual about connection between philosophy, science and values in various tradition.